Detection of Adult Celiac Disease Using Duodenal Screening Biopsies Over a 30-Year Period - Hugh James Freeman (Canadian Journal of Gastroenterology)
BACKGROUND: Serological studies suggest that celiac disease may be present in approximately 0.5% to 1% of the North American population. Screening data based on small intestinal biopsy performed during routine endoscopic evaluations are not available.